1986
DOI: 10.1088/0029-5515/26/5/001
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally inferred ion thermal diffusivity profiles in the Doublet III tokamak: Comparison with neoclassical theory

Abstract: Measurements of ion temperature profiles, obtained on a single-shot basis, have been coupled with transport analysis to obtain spatial profiles of the ion thermal diffusivity Xj for a series of 18 neutralbeam-heated discharges in the Doublet III tokamak. The expanded boundary divertor discharges examined in this study had the following range of parameters: B t = 2.53 T, I p = 0.35-0.89 MA, vertical elongation = 1.4-1.9, n e = (3.7-7.9) X 10 13 cm~3, P T = 3.5-6.6 MW, and v it ~ 0.03-0.22, for r/a = 0.2-0.7. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 42 publications
5
57
0
Order By: Relevance
“…The inferred ion thermal diffusivity is in general agreement with Chang-Hinton neoclassical values for these ohmically heated PLT plasmas and is consistent with earlier PLT results for Ohmic heating [2]. In neutral beam-heated Doublet III discharges [6] the diffusivity was about a factor of three larger relative to the neoclassical value than in our experiments, but the shapes of the PLT and Doublet III profiles are similar. The large errors in both experiments preclude a definite conclusion, but it seems likely that the difference in Xj is due to enhanced ion transport during neutral beam injection.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The inferred ion thermal diffusivity is in general agreement with Chang-Hinton neoclassical values for these ohmically heated PLT plasmas and is consistent with earlier PLT results for Ohmic heating [2]. In neutral beam-heated Doublet III discharges [6] the diffusivity was about a factor of three larger relative to the neoclassical value than in our experiments, but the shapes of the PLT and Doublet III profiles are similar. The large errors in both experiments preclude a definite conclusion, but it seems likely that the difference in Xj is due to enhanced ion transport during neutral beam injection.…”
Section: Resultssupporting
confidence: 91%
“…In DITE, charge exchange measurements by Gill et al [5] indicated ion heat fluxes about five times greater than predicted by neoclassical theory in both Ohmic and beam-heated discharges. Recent measurements using charge exchange recombination spectroscopy in heavily beam-heated Doublet III discharges [6] found that the ion heat conduction was comparable to Chang-Hinton [7] neoclassical conduction at r/a = 0.1 but exceeded the value from neoclassical theory by a factor of 3-13 at r/a = 0.5. One source of uncertainty in these measurements is uncertainty in the local gradient of the ion temperature, which was inferred from measurements of the ion temperature at a few points.…”
Section: Introductionmentioning
confidence: 95%
“…6 numerical results from comprehensive fully toroidal linear calculations (including complete trapped-particle dynamics, wave-particle resonant interactions, and collisions) support the conclusion that these modes are easily destabilized in tojcamaks for t^-> 2. 17 An appropriate expression for the anomalous thermal diffusivity associated with iij-modes is, of course, much more difficult to justify from "first principles.'…”
Section: Introductionmentioning
confidence: 65%
“…14 with regard to plasmas heated by neutral beam injection (NB1), data analysis again indicates that the ion thermal losses generally exceed standard neoclassical estimates. 15 Moreover, recent experimental studies 6 involving direct measurement of the ion temperature profile in the D-lll tokamak have indicated that the thermal diffusivity is not only much larger in magnitude but also exhibits a radial dependence in strong disagreement with the usual neoclassical model (Xj NE0 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stix's asymptotic expansion of Sivukhin's formula [19] yields similar results for r n . The expression given by Strachan et al [8] 1 - ri (1) T^ is the slowing-down time on electrons and E n is the energy at which the fusion reactivity has fallen to e" 1 of its value at E b .) The ~27% contribution of half-energy ions to the neutron emission was included in the calculation.…”
Section: Comparison Of Experimental and Theoretical Fast Ion Slowing-mentioning
confidence: 99%